Development of A Lexicon for Commercial Plain Sufu (Fermented Soybean Curd). Issue 1 (8th January 2016) - Chen, Yan Ping; Chung, Hau Yin
Abstract: Sufu (fermented soybean curd) is a cheese‐like product that is widely consumed in Asian countries. One of the subtypes is plain sufu, a traditional fermented food whose sensory attributes remain poorly characterized. In this study, we developed a lexicon for describing its sensory characteristics. Trained panelists evaluated the sensory profiles of 12 commercially available products manufactured in 3 locations. Sensory data were analyzed using one‐way analysis of variance and principal component analysis, and 8 aroma, 7 texture, 2 taste, and 5 flavor attributes were identified and defined. After further lexicon refinement, the aroma attributes salty, moldy, alcohol‐like, and meaty were identified to clearly differentiate fully aged samples from each other. The texture and flavor attributes that differentiate sufu were cohesiveness and sesame oil‐like, respectively. Practical Applications: The sufu lexicon helps product developers, researchers, and technologists understand the characteristics of plain sufu and those positive attributes when developing new, similar products and investigating quality‐control and shelf‐life topics. Because all mature plain sufus examined here presented similar sensory profiles derived from their major attributes, future studies could focus on distinct fermentation periods used to optimize products by employing the available definitions and references. Moreover, the developed lexicon can serve as a tool for correlating descriptive data to consumer preferences and to facilitating an understanding of the attributes that drive consumers' acceptance.